Spatial Planning Principles for Marine Ecosystem Restoration - Lester, Sarah E.; Dubel, Alexandra K.; Hernán, Gema; McHenry, Jennifer; Rassweiler, Andrew (Frontiers in Marine Science, 2020)
Coastal and marine ecosystems characterized by foundation species, such as seagrass beds, coral reefs, salt marshes, oyster reefs, and mangrove swamps, are rich in biodiversity and support a range of ecosystem services including coastal protection, food provisioning, water filtration, carbon sequestration, recreational opportunities, cultural value, among others. These ecosystems have experienced degradation and a net loss of total area in regions around the world due to a host of anthropogenic stressors, resulting in declines in the associated ecosystem services they provide. Because of the extensive degradation in many locations, increasing attention has turned to ecosystem restoration of these marine habitats. Restoration techniques for marine and coastal ecosystems are generally more expensive when compared to terrestrial ecosystems, highlighting the importance of carefully selecting locations that will provide the largest return on investment, not only for the probability and magnitude of restoration success, but also for ecosystem service outcomes. However, site selection and spatial planning for marine ecosystem restoration receive relatively little attention in the scientific literature, suggesting a need to better articulate how spatial planning tools could be incorporated into restoration practice. To the degree that site selection has been formally evaluated, the criteria have tended to focus more on environmental conditions beneficial for the restored habitat, and less on ecosystem service outcomes once the habitat is restored, which may vary considerably from site to site, or with more complex landscape dynamics and spatial patterns of connectivity. Here we 1) review the recent scientific literature for several marine ecosystems (seagrass beds, salt marshes, and mangrove swamps) to investigate the degree to which site selection or spatial planning principles are applied for marine ecosystem restoration at different spatial scales, 2) provide a conceptual overview of the rationale for applying spatial planning principles to marine ecosystem restoration, and 3) highlight promising analytical approaches from the marine spatial planning and conservation planning literatures that could help improve restoration outcomes. We argue that strategic site selection and spatial planning for marine ecosystem restoration, particularly applied at larger spatial scales and accounting for ecosystem service outcomes, can help support more effective restoration.